Acid Suppressive Drugs - Cheol Min Shin (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2022)
Histamine H2 receptor antagonists (H2RAs) suppress gastric acid production by blocking H2 receptors in parietal cells. Studies have shown that proton pump inhibitors (PPIs) are superior to H2RAs as a treatment for acid-related disorders, such as peptic ulcer disease (PUD) and gastroesophageal reflux disease (GERD). PPIs reduce gastric acid production by irreversibly inhibiting the H+/K+ ATPase pump, and they also increase gastric emptying. Although PPIs have differing pharmacokinetic properties, each PPI is effective in managing GERD and PUDs. However, PPIs have some limitations, including short plasma half-lives, breakthrough symptoms (especially at night), meal-associated dosing, and concerns associated with long-term PPI use. Potassium-competitive acid blockers (P-CABs) provide more rapid and profound suppression of intragastric acidity than PPIs. P-CABs are non-inferior to lansoprazole in healing erosive esophagitis and peptic ulcers, and may also be effective in improving symptoms in patients with non-erosive reflux disease. Acid suppressive drugs are the most commonly used drugs in clinical practice, and it is necessary to understand the pharmacological properties and adverse effects of each drug.